Advanced Glycation End Products Impair Ca2+ Mobilization and Sensitization in Colonic Smooth Muscle Cells via the CAMP/PKA Pathway - Ting Yu; Yun Wang; Dong Qian; Xiaomeng Sun; Yurong Tang; Xiaoxue Shen; Lin Lin (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Excessive production of advanced glycation end products (AGEs) has been implicated in diabetes-related complications. This study aimed to investigate the mechanism by which AGEs potentially contribute to diabetes-associated colonic dysmotility. Methods: Control and streptozotocin (STZ)-induced diabetic groups were treated with aminoguanidine (AG). The colonic transit time and contractility of circular muscle strips was measured. ELISA, immunohistochemistry and western blotting were used to measure Nε-carboxymethyl-lysine (CML) levels. Primary cultured colonic smooth muscle cells (SMCs) were used in complementary in vitro studies. Results: Diabetic rats showed prolonged colonic transit time, weak contractility of colonic smooth muscle strips, and elevated levels of AGEs in the serum and colon tissues. cAMP levels, protein kinase-A (PKA) activities, and inositol 1,4,5-trisphosphate receptor type 3 (IP3R3) phosphorylation were increased in the colon muscle tissues of diabetic rats, whereas RhoA/Rho kinase activity and myosin phosphatase target subunit 1 (MYPT1) phosphorylation were reduced. The inhibition of the production of AGEs (AG treatment) reduced these effects. In cultured colonic SMCs, AGE-BSA treatment increased IP3R3 phosphorylation and reduced intracellular Ca2+ concentration, myosin light chain (MLC) phosphorylation, RhoA/Rho kinase activity, and MYPT1 phosphorylation. The PKA inhibitor H-89 and anti-RAGE antibody inhibited the AGE-BSA–induced impairment of Ca2+ signaling and cAMP/PKA activation. Conclusion: AGEs/RAGE participate in diabetes-associated colonic dysmotility by interfering with Ca2+ signaling in colonic SMCs through targeting IP3R3-mediated Ca2+ mobilization and RhoA/Rho kinase-mediated Ca2+ sensitization via the cAMP/PKA pathway.